The potential dangers of sexually oriented businesses - Martinez, Phillip (Kansas State University, 2016)
An ongoing debate has taken place within the criminology and planning sectors. A major question that has been raised is, "Are sexually oriented businesses associated with high crime rates?" Though this may seem like an important topic for communities, there is currently a lack of empirical studies dealing with it. This report acts as a case study for San Francisco, California. The case study compares crime rates near ten strip clubs with crime rates to a fairly similar business, night clubs. The data that was used refers to crime that took place from 2012-2014, and includes most violent, property and public disorder crimes. In order to find out which type of business is more "dangerous", a percentage equation was used. The results from the percentage equation show the probability of crime incidents within 1,500 feet of a strip club or a night club. An example of a result from this equation is that on average, 3.67% of all of San Francisco’s "Public Drunkenness" incidents will take place within 1,500 feet of a night club. Meanwhile, 4.54% of San Francisco’s "Public Drunkenness" incidents will occur within 1,500 feet of a strip club. One can see that each business has its own percentage based off of public drunkenness crimes that occurred from 2012-2014. A GIS spatial analysis process, the Ordinary Least Squares (OLS), was also used. The OLS process factors crimes with demographics. This is useful for criminological studies because it can find a statistically significant relationship between things like assaults and the percentage of people living in poverty. The crimes were arranged in 18 categories ranging from kidnapping to domestic violence, from larceny to arson, etc. Results show that when viewing the numbers from the percentage equation, night clubs had higher percentages for 6 of the 18 crimes. The strip clubs showed higher percentages for the remaining 12 crime categories. When viewing the results from the GIS analysis, one can see if crime rates are determined by characteristics such as income, percentage of people receiving food stamps, proximity to strip clubs and more. This report will cover background literature regarding sexually oriented businesses. It will also show the methodology used for the San Francisco case study, as well as the results from the study.
Keywords: Sexually Oriented Businesses; Crime; California